2017
DOI: 10.1097/ede.0000000000000550
|View full text |Cite
|
Sign up to set email alerts
|

Commentary

Abstract: T he city is now regarded as primary form of settlement, accommodating over half the world's population and almost 75% of the european population. [1][2][3] Urbanization is continuing at rapid rates worldwide 4 and the world is currently witnessing its largest surge of urban growth in human history. 5 Cities have long been known to be society's predominant engine of innovation and wealth creation, yet they are also society's main source of crime, pollution, and disease. 6 In recent years, evidence has been eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 10 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…Past research has shown that environmental attributes (e.g., land use mix and safety) may influence people's physical activity (Haselwandter et al, 2015;Khreis, van Nunen, Mueller, Zandieh, & Nieuwenhuijsen, 2017;Saelens, Sallis, Black, & Chen, 2003), such as walking (Haselwandter et al, 2015;Saelens & Handy, 2008). Associations between area deprivation and outdoor walking levels may be a sign of different influences of environmental attributes on participants' outdoor walking durations in low-and high-deprivation areas.…”
Section: Application Of the Findingsmentioning
confidence: 99%
“…Past research has shown that environmental attributes (e.g., land use mix and safety) may influence people's physical activity (Haselwandter et al, 2015;Khreis, van Nunen, Mueller, Zandieh, & Nieuwenhuijsen, 2017;Saelens, Sallis, Black, & Chen, 2003), such as walking (Haselwandter et al, 2015;Saelens & Handy, 2008). Associations between area deprivation and outdoor walking levels may be a sign of different influences of environmental attributes on participants' outdoor walking durations in low-and high-deprivation areas.…”
Section: Application Of the Findingsmentioning
confidence: 99%
“…To promote outdoor walking levels, a growing body of literature has addressed the link between the built environment and walking [ 9 , 10 , 11 , 12 ]. Although the influences of the built environment on walking are not yet well understood [ 13 , 14 ], transportation and urban planning research has identified some relationships between neighborhood built environment and outdoor walking [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In an increasingly urban world, with almost 75% of the European population living in urban areas [ 1 ], urban planners and public health professionals need to work together [ 2 ] since various environmental exposures and lifestyles detrimental to health can be found in cities [ 3 ]. Natural spaces such as parks, gardens, urban trees, etc.…”
Section: Introductionmentioning
confidence: 99%